Linguistic Challenges in Multilingual Classroom at the Basic Level: Teacher's Perspective - Pant, Chandani (Far Western Review, 2025)
Classrooms in Nepal represent a vivid picture of cultural and linguistic diversity, making the medium of instruction a major challenge for both teachers and students. This study explores the difficulties teachers face in using mother tongues as the medium of instruction in multilingual classrooms, where content delivery becomes complex. A qualitative research design with a narrative inquiry method and purposive sampling was employed to understand the situation of multilingualism and its impact on teaching and learning. The study was conducted in Bedkot Municipality of Kanchanpur district, a multiethnic and multilingual society. To analyze challenges at the basic education level, six Tharu students (three girls and three boys) from three schools were selected, alongside interviews with six subject teachers and three principals. Additionally, three focus group discussions were held with classes six, seven, and eight to gain deeper insights. Findings revealed that Tharu students were less active and less confident in classroom participation. While they collaborated well in their mother tongue, their limited knowledge of Nepali and English hindered broader interaction and comprehension. Effective teaching and learning were found to depend on full and meaningful participation of all learners, which was restricted by the linguistic gap. The study highlights that the absence of local language teachers, teaching materials, scripts, and strategic plans has made the implementation of mother tongue instruction highly challenging. It suggests that policymakers introduce flexible language- in-education policies balancing mother tongue with Nepali and English, develop resources, train teachers in multilingual pedagogy, and involve parents to value both identity and opportunity.